2014
DOI: 10.1590/1982-021620145912
|View full text |Cite
|
Sign up to set email alerts
|

Aparelhos orais de protrusão mandibular ? IAH, eficiência do sono, sono REM e oxigenação de usuários

Abstract: Objetivo: avaliar parâmetros polissonográficos de pacientes com indicação para uso de AOPMs.Métodos: estudaram-se, retrospectivamente, os dados de prontuários com base em itens que compunham a polissonografia de 124 pacientes com idade entre 25 e 77 anos, que não estavam fazendo nenhum tratamento para distúrbios do sono. O estudo foi aprovado pelo Comitê de Ética em Pesquisa da instituição de origem (CAE n o 0378.0.133.000-10).Resultados: 46,8% dos pesquisados tinham diagnóstico de apnéia leve, 91,8% roncavam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Corroborating this finding, a study of patients referred for treatment of Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHOS) found that most of those who had poor sleep efficiency also had poor or no REM sleep, and the severity of OSAHOS was greater, i.e., the AHI was higher. 26 Regarding the correlations observed between the polysomnographic parameters in ►Table 3, the literature presents similar results to the ones presented in this study. A cohort of men from the United States demonstrated that RDI was inversely associated with REM sleep and SWS, and that increased SWS was accompanied by increased sleep efficiency values.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Corroborating this finding, a study of patients referred for treatment of Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHOS) found that most of those who had poor sleep efficiency also had poor or no REM sleep, and the severity of OSAHOS was greater, i.e., the AHI was higher. 26 Regarding the correlations observed between the polysomnographic parameters in ►Table 3, the literature presents similar results to the ones presented in this study. A cohort of men from the United States demonstrated that RDI was inversely associated with REM sleep and SWS, and that increased SWS was accompanied by increased sleep efficiency values.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating this finding, a study of patients referred for treatment of Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHOS) found that most of those who had poor sleep efficiency also had poor or no REM sleep, and the severity of OSAHOS was greater, i.e., the AHI was higher. 26…”
Section: Discussionmentioning
confidence: 99%